2014, No. 16, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Current issues on audit and controlAurelija Kustienė, Independent audit as a strategic tool to reduce the information asymmetry on the market, 10Rasa Kanapickienė, Control measures in the accounting of intangible assets of public sector entities, 19Daiva Tamulevičienė, The concept of controlling and its evolution, 28Rūta Klimaitienė, Kristina Rudžionienė, Andželika Verbliugevičiūtė, The effectiveness of ABC method in small companies, 40Financial analysis and evaluationJonas Mackevičius, Lukas Giriūnas, Model of evaluation of enterprise risk management, 55Jovita Jusytė, Irma Kamarauskienė, Public sector entities in the financial statements relative analysis: theoretical and practical aspects, 64Gintarė Labonaitė, Rasa Subačienė, Methodology for net profitability analysis, 79Lukas Giriūnas, Gintarė Giriūnienė, Research on entrepreneur identification, 89Gintarė Giriūnienė, Research on entrepreneurship indicators, 97Solutions in financial scienceErika Beniušytė, Aurelija Zonienė, Financial model of investments to fixed assets, 105Deimena Kiyak, Individual investor investment alternatives assessment criteria modelling, 114Jonas Mackevičius, Vilius Savickas, Prof. Vladas Jurgutis on banks: his insights and their development in works Lithuanian author‘s, 129Challenges in preparing specialists of accounting and financeRomualdas Valkauskas, Assessment competences professionals, 141Liucija Budrienė, Milda Kvekšienė, Audronė Meškelienė, Challenges and trends of recognition of accountants’ competences, 149Audronė Bagdonienė, Fausta Smolenskienė, Analysis of the accounting speciality collage graduates’ employment opportunities at the labour market in the context of the workforce supply and demand, 160Lina Kušleikienė, Renata Šivickienė, Usage of methods,  which  develop skills of entrepreneurship,  during financial field lectures at Siauliai State College, 172
Keywords: none